KEGIATAN PEREMPUAN BALI DI DAERAH ALIRAN SUNGAI (DAS) UNDA KABUPATEN KLUNGKUNG PROVINSI BALI - Ida Bagus Astika Pidada; I Nengah Mileh; Ni Ketut Sukiani (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2023)
The UNDA River watershed is located in Klungkung Regency, Bali. The Unda Watershed is located 1 Km in the east of the Amlapura City and 40 Km from Denpasar City. The local people call the Unda River watershed by Yeh Unda or Tukad Unda. The Unda River watershed has a depth of 80 cm to 1 meter, a width of 77 meters, a height of 75 meters with a river length of 24.400 meters with a water discharge ranging from 5.422 to 7.390 liters/second. This river is almost never dry because it originates from seven rivers such as: (1) Barak, (2) Bajing, (3) Mangening, (4) Krekuk, (5) Telagawaja, (6) Sah, (7) Masin. The upstream boundary is Telagawaja River and the downstream boundary ends at Banjar Karangdadi and Banjar Pesurungan in Kusamba, Dawan District, which directly empties into the sea, namely the Badung Strait. Before the Agung mountain erupted on February 18th, 1963, Balinese women’s activities in the Unda River watershed were agriculture. However, after the eruption the activities changed to excavation, opening stalls, raising cattle, selling sajen, flowers, incense, matches for religious ceremonies, planting bananas, papaya, and jackfruit. The routine activities that still survive in the Unda River watershed to this day are, such as: bathing, washing, and religious activities. This signifies that many opportunities for Balinese women is to carry out various kinds of business activities in this river. Keywords: Unda watershed; activity; Balinese women